Testing of preparations for protection of grain crops from pests in the Steppe of Ukraine - S. Semenov (Карантин і захист рослин)
Goal. To determine the agroeconomic efficiency of the system of maize and sorghum protection against major phytophages by preparations of different spectrum of action in the northern Steppe of Ukraine.